IMPLEMENTASI KURIKULUM DARURAT COVID-19 DI MA HIDAYATUL HUSNA BUTUH KRAS KEDIRI - Leni Nurindah Lailatul Fitriana; Muawanah (STAI Pelabuhan Ratu, 2022)
The pandemic period that occurred in 2020 due to the outbreak of the Covid-19 virus has threatened various worlds, especially in the territory of Indonesia. Causing major changes in the order of life, social conditions are no exception in the world of education. The programs that have been designed by the education unit as a guide in the implementation of learning activities, like it or not, have to change. With the Covid-19 pandemic, the government has also issued instructions, namely prohibiting people from doing crowding activities and activities that bring mass. So that this has a big impact on programs and learning processes that have existed so far. An example is the change from face-to-face learning to online learning. Learning is carried out remotely with the help of information and communication media (mobile or laptop) with the help of the internet. The existence of these changes requires madrasas to adapt to the learning paradigm starting from planning, implementing learning to evaluating learning outcomes. This research took place in Madrasah Aliyah Hidayatul Husna, Butuh Kras Kediri. It is important to know further how to implement the emergency curriculum in terms of curriculum management aspects of curriculum planning and implementation, while evaluation is not carried out.